Noninvasive Monitoring of mRFP1- and mCherry-Labeled Oncolytic Adenoviruses in an Orthotopic Breast Cancer Model by Spectral Imaging - Anton V. Borovjagin; Lacey R. McNally; Minghui Wang; David T. Curiel; Mary J. MacDougall; Kurt R. Zinn (Molecular Imaging)
Genetic capsid labeling of conditionally replicative adenoviruses (CRAds) with fluorescent tags offers a potentially more accurate monitoring of those virotherapy agents in vivo. The capsid of an infectivity-enhanced CRAd, Ad5/3, delta 24, was genetically labeled with monomeric red fluorescent protein 1 (mRFP1) or its advanced derivative, “mCherry,” to evaluate the utility of each red fluorescent reporter and the benefit of CRAd capsid labeling for noninvasive virus tracking in animal tumor models by a new spectral imaging approach. Either reporter was incorporated into the CRAd particles by genetic fusion to the viral capsid protein IX. Following intratumoral injection, localization and replication of each virus in orthotopic breast cancer xenografts were analyzed by spectral imaging and verified by quantitative polymerase chain reaction. Fluorescence in tumors increased up to 2,000-fold by day 4 and persisted for 5 to 7 weeks, showing oscillatory dynamics reflective of CRAd replication cycles. Capsid labeling in conjunction with spectral imaging thus enables direct visualization and quantification of CRAd particles in tumors prior to the reporter transgene expression. This allows for noninvasive control of CRAd delivery and distribution in tumors and facilitates quantitative assessment of viral replication. Although mCherry appeared to be superior to mRFP1 as an imaging tag, both reporters showed utility for CRAd imaging applications.